Assessing the Relevance of the Normative Theory of the Press in Contemporary Nigerian Media - Akinyeye Bolanle Olajumoke (Budapest International Research and Critics University, 2026)
This paper examines the relevance of the Normative Theory of the Press in contemporary Nigerian media, focusing on the balance between press freedom, social responsibility, and developmental objectives. The Normative Theory, which categorizes press systems into models such as the authoritarian, libertarian, social responsibility, and Soviet-communist frameworks, provides a conceptual lens for evaluating how media institutions operate within political, economic, and cultural contexts. In Nigeria, the media landscape has evolved from a state-controlled press to a dynamic, pluralistic environment characterized by private ownership, digital innovation, and a proliferation of social media platforms. The study explores how Nigerian journalists and media organizations negotiate the tension between exercising freedom of expression and fulfilling societal obligations, including promoting democracy, public accountability, and national development. It highlights the challenges posed by political interference, economic pressures, ethical lapses, and the rise of misinformation, which test the applicability of traditional normative frameworks. Drawing on recent media practices and regulatory policies as well as existing literature, the paper argues that while the Normative Theory of the Press remains a valuable analytical tool, its relevance in Nigeria requires adaptation to contemporary realities, particularly in the digital era where media influence extends beyond conventional print and broadcast platforms. The analysis contributes to scholarly debates on media ethics, governance, and development communication by demonstrating that normative principles must be contextually interpreted to guide responsible journalism in a rapidly changing Nigerian media environment.